Buschke-Lowenstein tumor: a case report - Yu. N. Kolbashova; D. V. Aphanasyev; S. Yu. Philosophov; V. V. Burtsev (Тазовая хирургия и онкология, 2019)
Buschke-Lowenstein tumor caused by human papilloma virus is a rare sexually transmitted disease of the anogenital region. Being histologically benign, clinically giant condyloma acuminatum exhibits malignant properties by adhering to surrounding tissues, and a high recurrence rate. However, no clear diagnostic criteria and surgical approach description has been detected for this condition. This clinical observation demonstrates a rare case of Buschke-Lowenstein tumor and the multi-stage surgical treatment, resulting in failure.